An Analysis Of Traffic Accident Charachteristic In Rimbo Panjang-Bangkinang Road, Kampar District, Riau Province - Abdul Kudus Zaini (Strategic: Journal of Management Sciences, 2021)
Kampar is a district in Riau Province which has 841.332 people. (BPS : 2019). As long as the society’s growth over Kampar District, the need of transportation system is also increased, which makes accidents number increased every year. By the term of condition, some handling operations are needed to know the capacity and rank of accident-prone areas to reduce traffic accidents. This study used secondary data from local police agency by accidents data from 214-2018. Data were analyzed to count the accident-prone areas. The total numbers of accident rate was on Jalan Rimbo Panjang-Bangkinang with the total 53 accidents. There were 99 victims of whom 18 people wee died, 32 people were seriously injured and 49 were slightly injured. It observed by Blacks Spot and Black Site methods. Based on Accident rate, roads on Rimbo Panjang-Bangkinang were identify by Accident Rate 0,399. Sei Tiarap-Kampar Village on Accident Rate 0,233 and Penyesawan Village – Air Tiris by Accident Rate 0,233 And Clack Site 0,133 for Padang Mutung-Village-Penyesawan Village. 0,116 for Sei Tiarap – Kampar Village and 0,033 for Penyesawan-Air Tiris. The conclusion is there are three accident-prone areas from thirteen locations, which makes handling and addition of facilities and infrastructure should be done, as well as development of traffic discipline of road users.